2020
DOI: 10.1177/1071100720955155
|View full text |Cite
|
Sign up to set email alerts
|

Bone Cysts and Osteolysis in Ankle Replacement

Abstract: Background: Total ankle replacements (TARs) have higher rates of osteolysis than hip or knee replacements. It is unclear whether this is a pathologic immunologic process in response to wear debris, or expansion of pre-existing osteoarthritic bone cysts. We aimed to determine the incidence of bone cysts in patients with end-stage ankle arthritis prior to surgery and review the literature on bone cysts and osteolysis in relation to TAR. Methods: This is a descriptive/prevalence study in which all patients with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…These early cysts may be preoperative bone cysts rather than procedure-related osteolytic cysts. 47 In our study, the average time of diagnosis was 7.1 years after the TAA procedure, ranging from 3.7 to 9.7 years. These were thus late-onset cysts, which lead us to believe that these cysts would have progressed in size, ultimately leading to mechanical failure.…”
Section: Discussionmentioning
confidence: 61%
“…These early cysts may be preoperative bone cysts rather than procedure-related osteolytic cysts. 47 In our study, the average time of diagnosis was 7.1 years after the TAA procedure, ranging from 3.7 to 9.7 years. These were thus late-onset cysts, which lead us to believe that these cysts would have progressed in size, ultimately leading to mechanical failure.…”
Section: Discussionmentioning
confidence: 61%
“…4,8,15,18,38 With progressive cysts, the risk for component revision or conversion to arthrodesis is substantial, and it is generally recommended to closely follow TAR patients with sufficient imaging modality. It has been shown that CT shows osteolytic lesions around TAR significantly better than radiographs, 16,17,30,36 especially on the talar side, 17 and also in the previously mentioned study by Najefi et al, 29 the preoperative cysts were not detected on plain radiographs in 60% of the cases. The radiation dose not cause a major problem as the ankle is located peripherally and the mean effective dose for CT of the ankle is only 0.07 mSv.…”
Section: Discussionmentioning
confidence: 66%
“…In a series of 120 consecutive patients with end-stage ankle osteoarthritis analyzed with CT prior to TAR, 78% of patients had bone cysts present in the area where they would not have been removed by bone resection at surgery, located mainly in medial and lateral malleoli. 29 The authors concluded that a preoperative 3-dimensional imaging to detect the existence of preoperative cysts in TAR patients would be useful when assessing the cysts postoperatively. 29 In the current study, all the osteolytic lesions detected on CT images developed postoperatively, and none of them were seen on preoperative CT or MRI images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations